Emerging Retail Formats and its attributes: An insight to convenient shopping (Global Journal of Management and Business Research, 2012)
Purpose: The present paper tries to understand the improvement in retail sector in India, especially the modern retail formats, its attribute, type of goods and impact of consumers#x2019; demography on choice of emerging retail formats. Methodology: A self-structured questionnaire has been used for collecting the data from 100 urban consumers of three major cities of Punjab i.e. Jalandhar, Amritsar and Ludhiana. Stratified random sampling method has been used for the study. Findings: The findings of the paper reveal that consumers#x2019; prefer modern retail formats due to its significant product attributes like improved quality, variety of brands and assortment of merchandise and store attributes like parking facility, trained sales personnel and complete security. The major results of the study depict that consumers prefer malls and specialty store to purchase various shopping goods like clothing, footwear and jewellery. Further the results highlight that the modern retail formats are extremely preferred by young consumer#x2019;. Originality: The paper is first of its kind to take all the important aspects together like modern retail formats, type of attributes and products and the demographic profile of consumers#x2019;. With all these aspects, paper tries to study the changing consumers#x2019; behavior towards shopping from the modern retail formats.
Keywords: Retail formats; Attributes; Shopping; Convenience; Products; Consumers#x2019; and Demography